A economia das doenças raras e o caso da Doença de Machado-Joseph : aspectos epidemiológicos, custos econômicos associados e a oferta de cuidadores no Rio Grande do Sul - Silva, Cristiane da (2022)
This thesis aims to investigate rare diseases, in particular Machado-Joseph Disease (MJD), from the perspective of health economics in terms of epidemiological aspects, care needs and direct and indirect costs. In order to contextualize the research problem, the first essay presents a narrative review, characterizing rare diseases and especially Machado-Joseph’s Disease (MJD). Its prevalence and the importance of a care network for patients with MJD are highlighted, as well as the public policies adopted in relation to this type of disease. It was found that there is no single definition for rare diseases and that the production of medicines involves research, risks and high costs, but also generates individual, social and economic benefits. Rio Grande do Sul has a high prevalence of MJD, justified by the founder effect, which corresponds to the loss of genetic variability in a given population composed of a very small number of individuals. There were also several difficulties encountered by patients and their families given the fragility associated with access to diagnosis. As it is a hereditary disease, studies involving prenatal and preimplantation diagnoses were highlighted, because both diagnoses are capable of interrupting the continuity of new generations with the disease. For this reason it is believed that families should be informed about these possibilities. The second trial estimates the direct and indirect health-related costs due to lost productivity attributable to MJD from a societal perspective. Bottom-up cost analysis is used as a methodology. The results showed that 70,51% of patients undergoing rehabilitation have some associated cost. While 68,81% have medication and diaper costs and 6,42% have caregiver costs. For the year 2020, the total annual direct costs per patient were estimated at R$ 9.871,90. The total annual indirect costs with retirement and social security benefits amounted to R$ 1.830.954,00. In addition, it was found that most of the interviewees no longer have a professional activity and receive some social assistance. Another important data refers to the number of children, 74,3% of the sample reported having one to three children and 95,41% of respondents reported having at least one case of MJD in the family. Such information reinforces the argument that actions are needed with families regarding family planning, since the high genetic burden of transmission causes the costs of the disease to be perpetuated, compromising many generations in the same family. Finally, the third trial estimates the chances, by degree of kinship, given the characteristics of the patients, in order to identify the financial consequences of the 2 disease for the patient and the caregiver, which, in most cases, sometimes it is part of the family composition. Finally, the third trial estimates the chances of having a caregiver, by degree of kinship, given the characteristics of the patients, in order to identify the financial consequences of the disease for the patient and the caregiver, which, in most cases, sometimes it is part of the family composition. Among the results found, it was found that the patient is male, education, the number of family members who have already had the disease, the natural logarithm of total income and the distance the patient is from the capital reduce the chances of caregiver being the patient's child compared to the patient who has no caregiver. On the other hand, advancing age, being single, the number of living children and whether the patient uses any device or support instrument to walk increases the chance that the caregiver will be a child. compared to the patient who has no caregiver. Regarding the category that reports the caregiver as the patient's husband, it appears that, the patient being male, advancing age, education, being single, the number of living children and the number of of family members who have already had the disease reduce the chances of the caregiver being the patient's spouse compared to the patient who does not have a caregiver. Meanwhile, the natural logarithm of total income, the distance the patient is from the capital and whether the patient uses some instrument or support to walk increases the chance of the caregiver being a spouse compared to the patient who does not have a caregiver. For the category in which the caregiver is the mother, father or other family member, it was found that being single, the number of family members who have already had the disease and the distance that the patient is from the capital increase the chances that the caregiver is a mother, parent or other family member.